Perspectives on research in goats in the Asian and the Pacific - Devendra, C. (Institut de l'Elevage, 2000)
An overview of research in the Asia and Pacific region is presented with reference to its features and direction. Much of the research has been undertaken along disciplinary lines. The overriding emphasis is on feeding and nutrition, genetic improvement and animal health with little reference to real farm situations and relevance to production systems and agro-ecological zones. Resource use for research by national programmes and donor agencies is generally weak, despite the considerable opportunities and challenges.